Board Diversity and Firm Value: Evidence From Nepalese Financial Institutions - Thapa, Rajendra (INTELLIGENCE Journal of Multidisciplinary Research, 2024)
The purpose of this paper is to provide empirical evidence on the relationship of board diversity of corporate board with the value of financial institutions in Nepal. The sample comprises 38 financial institutions listed in NEPSE with 380 firm-years observation for the period 2011/12 to 2020/21. Balance panel datasets were employed to investigate using multiple regression models to examine the relationship between board diversity (female and minority directors) and firm value measured by Tobin's Q and MBR. The result shows a significant positive relationship between firm value and the presence of both female and minority directors. Moreover, the evidence supports that the presence of female directors in the boardroom effect more in the firm market value than as compare to the minority directors. Furthermore, the study concludes that control variables like board size, presence of independent director and firm size have positive significant effect on firm value, but leverage has significant but negative relation with the firm market value of financial intuitions in Nepal. The study result has the practical implication for government, policy makers and regulating authorities in formation of diverse board that can increase the firm value and performance. It also provides additional insight to the corporate governance literature and helps to fill the gap on board diversity and firm value in Nepalese financial institutions.